Faktor yang Berhubungan dengan Kecelakaan Kerja pada Pekerja Bengkel Las di Distrik Abepura Kota Jayapura - Mudasir, Aisyah; Medyati, Novita; Irjayanti, Apriyana (Faculty of Medicine, Universitas Andalas, 2022)
The welding industry is part of the informal sector industry whose work is associated with many hazards and risks that can increase the number of work accidents. With the increasing cases of work accidents, it is necessary to look for the causes or things that influence them so that prevention and mitigation efforts can be carried out. Objective: To determined the factors associated with work accidents among welding workshop workers in the Abepura District, Jayapura City. Methods: This research was conducted in an analytic observational manner with a cross-sectional design. The location of this research was carried out at welding workshops in the Abepura District, totaling 12 workshops. The sample of this research is 41 workers selected by purposive sampling technique. Data were analyzed using univariate and bivariate with a chi-square test. Results: The study showed that there was no relationship between age p = 0.671 (p>0.05) and education p = 1.000 (p>0.05) with the incidence of work accidents among welders. There was a relationship between years of service p = 0.033 (p<0.05), knowledge p=0.001 (p<0.05), and unsafe actions p=0.027 (p<0.05) with occupational accidents in welders. Conclusion: There is a relationship between years of service, knowledge, and unsafe actions with work accidents.Keywords: Â welding workshop, Â work accidents, workerÂ